Two new species of South American freshwater crayfish genus Parastacus Huxley, 1879 (Crustacea: Decapoda: Parastacidae) - Ribeiro, Felipe Bezerra; Buckup, Ludwig; Gomes, Kelly Martinez; Araujo, Paula Beatriz (Zootaxa, 2016)
Two new species of Parastacus Huxley, 1879 are described from material collected in the state of Rio Grande do Sul, southern Brazil: Parastacus fluviatilis sp. nov. from highland streams and Parastacus caeruleodactylus sp. nov. from wetlands. Parastacus fluviatilis sp. nov. is distinguished mainly by large chelipeds with dense setae cover on the cutting edge of fingers, telson subtriangular with two lateral blunt spines and strongly concave ventral surface of lateral process of thoracic sternites 6 and 7. Parastacus caeruleodactylus sp. nov. is distinguished mainly by blue cheliped fingers and a large gap between them, reduced abdomen, dorsal and ventral margins of dactylus, propodus and carpus of second pair of pereiopods with tufts of long setae and mid-dorsal carina of exopod of uropods unarmed. According to IUCN Red List criteria both species are considered endangered. Habitat characterization and a method for defining the shape of second abdominal pleura are also provided.